Insulin Resistance in Osteoarthritis: Similar Mechanisms to Type 2 Diabetes Mellitus - Elena V Tchetina; Galina A Markova; Eugeniya P Sharapova (Journal of Nutrition and Metabolism)
Osteoarthritis (OA) and type 2 diabetes mellitus (T2D) are two of the most widespread chronic diseases. OA and T2D have common epidemiologic traits, are considered heterogenic multifactorial pathologies that develop through the interaction of genetic and environmental factors, and have common risk factors. In addition, both of these diseases often manifest in a single patient. Despite differences in clinical manifestations, both diseases are characterized by disturbances in cellular metabolism and by an insulin-resistant state primarily associated with the production and utilization of energy. However, currently, the primary cause of OA development and progression is not clear. In addition, although OA is manifested as a joint disease, evidence has accumulated that it affects the whole body. As pathological insulin resistance is viewed as a driving force of T2D development, now, we present evidence that the molecular and cellular metabolic disturbances associated with OA are linked to an insulin-resistant state similar to T2D. Moreover, the alterations in cellular energy requirements associated with insulin resistance could affect many metabolic changes in the body that eventually result in pathology and could serve as a unified mechanism that also functions in many metabolic diseases. However, these issues have not been comprehensively described. Therefore, here, we discuss the basic molecular mechanisms underlying the pathological processes associated with the development of insulin resistance; the major inducers, regulators, and metabolic consequences of insulin resistance; and instruments for controlling insulin resistance as a new approach to therapy.